Genetic characteristic of protein membran of avian influenza viruses H5N1 subtype - Dharmayanti, N.L.P Indi; Hewajuli, D.A; Ratnawati, A; Indriani, R; ., Darminto (Indonesian Journal of Animal and Veterinary Sciences, 2010)
In 2006-2008 there were findings about the antigenic drift on AI virus due to vaccination and the AI H5N1 subtype viruses which was similar to H5N1 viruses in human. The findings indicated that the AI viruses continue and undergoing to mutate and try to adapt with their environment.Â  The objective of this study was to characterize the mutation of recent AI viruses (2009) on the membran protein namely Hemagglutinin (HA), Neuraminidase (NA) and Matrix 2 (M2). In this study RT-PCR â sequencing methods and genetic analysis for the protein membran of AI viruses were used. Result revealed that there were specific mutation belong to AI 2009 viruses on HA and NA protein such as AI virus mutation in 2008 which was isolated from backyard chicken. The mutations were non synonimous and not caused by immunological pressure. Furthermore, M2 analysis indicated that the viruses were resistant to amantadine. Key Words: Mutation, AI Subtype H5N1 Viruses, Membran Protein